2020
DOI: 10.1093/cid/ciaa1748
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Outcomes of Hospitalized Patients With Severe Coronavirus Disease 2019 (COVID-19) and Secondary Bloodstream Infections: A Multicenter Case-Control Study

Abstract: Background Coronavirus disease 2019 (COVID-19) has become a global pandemic. Clinical characteristics regarding secondary infections in patients with COVID-19 have been reported, but detailed microbiology, risk factors, and outcomes of secondary bloodstream infections (sBSIs) in patients with severe COVID-19 have not been well described. Methods We performed a multicenter case-control study including all hospitalized patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
84
3
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(102 citation statements)
references
References 28 publications
8
84
3
7
Order By: Relevance
“…To our knowledge, to date, this issue remains under-investigated. A large multi-centric cohort study including only COVID-19 highlighted that the most common presumed source was unknown or not reported [ 30 ]. Moreover, the role of bacterial translocation should further be evaluated: a recent monocentric Italian study showed an increased risk for enterococcal BSI among COVID-19 patient, thus suggesting an enteric involvement in patients with severe COVID-19 [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, to date, this issue remains under-investigated. A large multi-centric cohort study including only COVID-19 highlighted that the most common presumed source was unknown or not reported [ 30 ]. Moreover, the role of bacterial translocation should further be evaluated: a recent monocentric Italian study showed an increased risk for enterococcal BSI among COVID-19 patient, thus suggesting an enteric involvement in patients with severe COVID-19 [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the prevalence of COBSI was 8.6%, which was higher than previously reported rates of 1.6%-2.5%. 1,3,4 Previous studies did not report nursing home admissions. In our study, 30% of COVID-19 patients were admitted from the nursing homes.…”
Section: Discussionmentioning
confidence: 99%
“…Despite Northern NJ being an early epicenter (March, 2020) in the US for COVID-19, which rapidly engulfed the entire state, there has been a paucity of research on the epidemiology of this disease in the NJ population. At the time of writing, only three studies were published to fill this gap, with one describing the clinical features in a minority patient population, one investigating the impact of COVID-19 on mothers, infants and staff in a delivery service in NJ, and one focusing on the secondary bloodstream infections in severe COVID-19 patients 14 16 . Contributing to this growing knowledge base, our study describes the clinical characteristics and outcomes in a large hospitalized patient series in our hospital network covering Northern NJ, during the early phase of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%